2022
DOI: 10.1590/fst.64921
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and antifungal properties of essential oils of oregano (Origanum vulgare) and mint (Mentha arvensis) against Aspergillus flavus and Penicillium commune for use in food preservation

Abstract: This study determined the chemical composition and evaluated the antioxidant activity and antifungal properties of essential oils of oregano (Origanum vulgare) and mint (Mentha arvensis) against the fungi Aspergillus flavus and Penicillium commune as possible alternatives for food preservation. The antimicrobial activity of both oils is shown by their minimum inhibitory concentration (4 mg/mL) for oregano oil, and (8 mg/mL) for mint oil, and minimum inhibitory dose (< 110 µl/L) for oregano oil, and (< 1500 µL/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 63 publications
1
6
0
3
Order By: Relevance
“…It can be concluded that the concentration of essential oil compounds varies depending on the time of harvest, growing conditions, geographical location, altitude, climate, genetic diversity and phenological age of the plant at the time of cutting [14]. According to Almeida et al [15]the IC50 value for oregano oil is 0.5 mg/mL, which is almost the same value as in this study. From the presented results, it can be seen that synthetic antioxidants have a higher antioxidant capacity than natural ones.…”
Section: Resultssupporting
confidence: 79%
“…It can be concluded that the concentration of essential oil compounds varies depending on the time of harvest, growing conditions, geographical location, altitude, climate, genetic diversity and phenological age of the plant at the time of cutting [14]. According to Almeida et al [15]the IC50 value for oregano oil is 0.5 mg/mL, which is almost the same value as in this study. From the presented results, it can be seen that synthetic antioxidants have a higher antioxidant capacity than natural ones.…”
Section: Resultssupporting
confidence: 79%
“…It should be added that OEO composition can be modified by ontogenetic factors [ 17 ], environmental factors [ 18 ], and production conditions [ 5 , 19 ]. Carvacrol, β-caryophyllene, o-cymene, γ-terpinene, linalool and thymol are mentioned as primary components of OEO [ 3 , 5 ]. Among the main constituents of OEO, carvacrol, a compound with broad biological activity, including antioxidant and antimicrobial activity, occupies a special place [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Oregano is a good source of natural antioxidants with potential use in the food and pharmaceutical industries as a safer alternative to synthetic antioxidants [ 20 , 21 ]. The AA of the essential oil obtained from oregano herb is estimated by the DPPH method to be approximately 60–70% [ 3 , 14 ]. The stable DPPH radical is often used to determine the AA of single compounds as well as extracts obtained from plant material [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EOs are a combination of nonvolatile and volatile natural compounds which have antimicrobial and antioxidant properties (Bakkali et al, 2008). Many investigations have been made by many researchers on the chemical contents (Shin et al, 2022), antimicrobial (Chikhoune et al, 2013) and antifungal properties (Almeida et al, 2022) of different Eos. The EOs are approved as antimicrobial agents against several pathogenic and spoilage microorganisms involved in foodborne diseases (Aydogdu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%